2020
DOI: 10.1371/journal.pone.0239152
|View full text |Cite
|
Sign up to set email alerts
|

A tissue engineering approach for repairing craniofacial volumetric muscle loss in a sheep following a 2, 4, and 6-month recovery

Abstract: Volumetric muscle loss (VML) is the loss of skeletal muscle that results in significant and persistent impairment of function. The unique characteristics of craniofacial muscle compared trunk and limb skeletal muscle, including differences in gene expression, satellite cell phenotype, and regenerative capacity, suggest that VML injuries may affect craniofacial muscle more severely. However, despite these notable differences, there are currently no animal models of craniofacial VML. In a previous sheep hindlimb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Because skeletal muscle regeneration largely resembles embryonic muscle development, a significant disparity exists between adult myogenesis in craniofacial and limb muscle regeneration. Craniofacial MuSCs exhibit distinct behaviors both in a homeostatic state and in response to acute and chronic stimuli ( Ono et al, 2010 ; Keefe et al, 2015 ; Rodriguez et al, 2020a , b ).…”
Section: The Architect Of Muscle Regeneration: Satellite Cellsmentioning
confidence: 99%
“…Because skeletal muscle regeneration largely resembles embryonic muscle development, a significant disparity exists between adult myogenesis in craniofacial and limb muscle regeneration. Craniofacial MuSCs exhibit distinct behaviors both in a homeostatic state and in response to acute and chronic stimuli ( Ono et al, 2010 ; Keefe et al, 2015 ; Rodriguez et al, 2020a , b ).…”
Section: The Architect Of Muscle Regeneration: Satellite Cellsmentioning
confidence: 99%
“…It might aid in the advancement of tissue engineering-based therapies for VML [45]. An experimental model of VML has suggested that an appropriate model should be selected for VML studies considering various factors including volume of muscle removed, the location of the VML injury, and the geometry of the injury [12]. Additionally, different strategies including various biomaterials are under consideration in experimental models designed to enhance the therapeutic outcomes of both cell and growth factor-based approaches in VML, for example, larger animal models may provide a better VML model as compared to small lab animals.…”
Section: Tissue Engineering In Vmlmentioning
confidence: 99%
“…Additionally, different strategies including various biomaterials are under consideration in experimental models designed to enhance the therapeutic outcomes of both cell and growth factor-based approaches in VML, for example, larger animal models may provide a better VML model as compared to small lab animals. In this direction, Rodriguez and his team use the sheep as a craniofacial VML model to highlight the importance of a clinically realistic model [12].…”
Section: Tissue Engineering In Vmlmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 , 24 ] Studies have been conducted on VML on craniofacial muscles of large animals, such as zygomaticus muscles of sheep, emphasizing the pathophysiological differences between limb and craniofacial VML. [ 25 ] However, a craniofacial VML mouse model using actual craniofacial muscles has not been reported yet due to the small size of the craniofacial muscles of a mouse. A potential challenge in developing the craniofacial VML mouse model is the lack of functional assay tools that can monitor the regeneration and recovery of injured craniofacial muscles in the active mouse in a noninvasive manner.…”
Section: Introductionmentioning
confidence: 99%